An evolutionary and developmental biology approach to gastroschisis. Issue 6 (28th February 2019) - Opitz, John M.; Feldkamp, Marcia L.; Botto, Lorenzo D.
Abstract : Recent advances have now made it possible to speak of gastroschisis narrowly in morphogenetic terms invoking the Rittler–Beaudoin (R–B) model. This proceeds from the appreciation of gastroschisis as a congenital intestinal herniation (without cover or liver) within the primordial umbilical ring, mostly to the right side of a normally formed umbilical cord. Presently, it is unresolved whether this visceral prolapse represents failure of ring closure before return of the physiological hernia into the abdomen or rupture of the delicate amniotic/peritoneal membrane at the ring's edge to the right of the cord. Animal observations and experiments will be required to address this question effectively. If gastroschisis is, in fact, a primary malformation with the primordial umbilical ring as the developmental field involved, then homology implies potential gastroschisis in all amniotes with corresponding nourishment from yolk sac (aka omphalomesenteric) vessels going into the embryo and excretory products out via the ancient umbilical connection. It also implies homology of corresponding morphogenetic signal transduction cascades. We review the history of gastroschisis, its presumed pathogenesis, and the developmental biology of the amniotic umbilical ring from this perspective. Therefore, based on the animal and human evidence to date, we propose that gastroschisis is a primary midline malformation that involves the umbilical canal from amniotic to peritoneal space and its primordial umbilical ring, either through nonclosure or rupture of the membrane covering the area, mostly to the right, between the cord and the edge of the ring.